PENGARUH LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi kasus di Desa Wringin Anom, Desa Sumberkolak, Desa Paowan Kecamatan Panarukan Kabupaten Situbondo) - Moh. Arif Setiawan; Ediyanto Ediyanto; Minullah Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of work environment and leadership on the performance of village officials with job satisfaction as an intervening variable. This study uses a quantitative approach with explanatory methods. The population in this study were all village officials in three villages in the Panarukan District, Situbondo Regency, totaling 45 people. The sampling technique used saturated samples, where all members of the population were sampled. Data analysis and hypothesis testing used Partial Least Square Structural Equation Modeling (PLS- SEM) with the SmartPLS 3.0 application. The results showed that the work environment had a positive and significant effect on job satisfaction, but leadership had no significant effect on job satisfaction. Work environment and leadership have no significant effect on performance. Job satisfaction also has no significant effect on performance. Furthermore, work environment and leadership have no significant effect on performance through job satisfaction. This study concludes that a good work environment can increase the job satisfaction of village officials, but effective leadership still needs to be improved. Job satisfaction has not been able to become a significant mediation in improving the performance of village officials. This study recommends that village governments pay more attention to factors that can increase job satisfaction and leadership effectiveness, as well as create a conducive work environment to improve the performance of village officials. Further research can expand research variables and research context to gain a more comprehensive understanding.